2017
DOI: 10.1002/stem.2692
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Phenotyping Reveals Heterogeneity Among Hematopoietic Stem Cells Following Infection

Abstract: The hematopoietic stem cell (HSC) niche provides essential microenvironmental cues for the production and maintenance of HSCs within the bone marrow. During inflammation, hematopoietic dynamics are perturbed, but it is not known whether changes to the HSC-niche interaction occur as a result. We visualize HSCs directly in vivo, enabling detailed analysis of the 3D niche dynamics and migration patterns in murine bone marrow following Trichinella spiralis infection. Spatial statistical analysis of these HSC traje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
(92 reference statements)
1
17
0
Order By: Relevance
“…The CD317 expression pattern is providing the first direct evidence that all HSCs rapidly react to IFN, suggesting that the bone marrow niche is highly permeable in the context of immune stimulation. The observed heterogeneity in CD69 expression is in agreement with a functional heterogeneity among HSCs following infection [ 6 ], and suggests future functional assessment of HSC’s sub-populations. Interestingly, a very-recent study demonstrated potential mobilization and activation of HSCs and progenitors in a human-CD69 mouse model [ 15 ], suggesting further interest in this receptor.…”
supporting
confidence: 59%
“…The CD317 expression pattern is providing the first direct evidence that all HSCs rapidly react to IFN, suggesting that the bone marrow niche is highly permeable in the context of immune stimulation. The observed heterogeneity in CD69 expression is in agreement with a functional heterogeneity among HSCs following infection [ 6 ], and suggests future functional assessment of HSC’s sub-populations. Interestingly, a very-recent study demonstrated potential mobilization and activation of HSCs and progenitors in a human-CD69 mouse model [ 15 ], suggesting further interest in this receptor.…”
supporting
confidence: 59%
“…These aged HSCs may arise from either the cell-intrinsic transition of balanced to myeloid-biased LT-HSCs or the clonal expansion of preexisting fractions of myeloid-biased LT-HSCs (13,14,16,20,21). Several studies support the presence of preexisting myeloid-biased LT-HSCs by demonstrating that myeloid-biased subpopulations of LT-HSCs in young, healthy mice respond to environmental challenges, such as inflammation and infection (22,23). Results from lineage tracing with genetic barcodes (24,25) and single cell transplants of LT-HSCs also support the notion of inherent functional diversity among LT-HSCs (26)(27)(28).…”
mentioning
confidence: 99%
“…Previous studies have shown that a subpopulation of pHSCs expands with age 15,23 and responds to environmental challenge 18,19 . However, the effect of aging and stress on LT-HSCs and their subpopulations have not yet been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Although Hoxb5 + LT-HSCs are long-term self-renewing cells, it is unknown whether they contain fractions with distinct functional properties. Increasing evidence suggests that subpopulations of LT-HSCs selectively respond to environmental stress conditions 18,19 and exhibit biases in lineage contribution 18 . Moreover, the selective and clonal expansion of a subset of LT-HSCs has been proposed to mediate the changes observed in hematopoiesis during aging 15,54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation